Animal study: A comparative evaluation in the safety of mesh hydrogel and hydrocolloid for partial thickness wound of skin - Pinchai, Opart; Sirimaharaj, Wimon; Nalumpang, Kanarat; Molloid, Robert; Sananpanich, Kanit; Yusuk, Amnat (Biomedical Sciences and Clinical Medicine, 2017)
Objective To compare the safety of mesh hydrogel and hydrocolloid for partial thickness wound of skin in rats. Methods Twelve rats were used in this study, 6 rats for control group and 6 rats for study group. In the control group, 0.5 cm diameter skin abrasion was created on the right side of back. The hydrocolloid were applied on the abrasion of right side and applied on the intact skin of left side of back of rats. In the study group, 0.5 cm diameter skin abrasion was created on the right side of back. The mesh hydrogel were applied on the abrasion of right side and applied on intact skin of left side of back of rats. The evaluations are [1] Dermal irritancy [2] Histologic change [3] Liver function [4] Kidney function. Results There is no signi fi cant difference of erythema and edema on the abrasion or intact skin of rats between two groups at 24 and 72 hours after applying the dressing materials. There are no signi fi cant differences of histologic change, liver function and kidney function between two groups. Conclusion There is no signi fi cant difference in safety of mesh hydrogel and hydrocolloid for partial thickness wound of skin in rats.